360. Paramed MR Open installation: Customized quality assurance protocol and safety issues. (December 2018) - Poggiu, A.; Bona, R.; Pinna, F.; Marini, P.
Abstract : Purpose: MR Open produced by Paramed is an open MRI total body scanner, with a static maximum field of 0, 5 T, and a superconducting MgB2 coils system, not requiring a liquid helium bath. A recent installation in ASSL Sassari has permitted to investigate the performance of the scanner and a different approach to safety problems. Methods and materials: MGB2 is an intermetallic superconductor (Tc 39 K, instead of about 10 K for Nb-Ti classical magnets) recently used in MRI, through two cryocooling systems exploiting a small amount of helium gas in two closed-loops. Our MR open has an open magnet, and is equipped with 10 different multichannel coils, addressed to patients' multiposition and weight-bearing studies, while cardiac and breast studies are not permitted. The scanner is suitable for claustrophobic and wheelchair patients. A specific quality assurance protocol has been assessed for each coil, according to EUROSPIN, NEMA, and AAPM guidelines. EUROSPIN phantoms have been used in general, but two ESAOTE (not PARAMED) phantoms have proved useful for the smaller coils. Results: The amount of helium was judged safe: even in case of total dispersion, oxygen level wouldn't drop down 20, 6%: unexpected quench problems are substantially fictitious, no quench line and oxygen sensor are needed. Magnetic fringe field is quite high. The possibility to quickly switch off the static field should be managed carefully, even in case of accident: the hazard of high induced currents should be considered. The quality parameters resulted within AAPM tolerances for all the coils, SNR values were determined according to NEMA and kept as reference, maximum ghosting resulted in 2, 5%, higher than usual. Conclusion: Safety and QA protocols must be fit to the particular facility. The comprehensive phantom set resulted quite appropriate, except for the spatial resolution with small coils (only 2 mm possible measure). Ghost is generally not negligible.